IEEE Std 802.3bg-2011 (Amendment to IEEE Std 802.3-2008). IEEE Standard for Information technology-- Local and metropolitan area networks-- Specific requirements (IEEE, 2011)
This amendment to IEEE Std 802.3-2008 specifies a new Physical Medium Dependent (PMD) sublayer, 40GBASE-FR, for serial 40 Gb/s operation over up to 2 km of single-mode fiber. Keywords: 40 Gb/s Ethernet, 40GBASE-FR, IEEE 802.3bg, Optical Transport Network, OTN, Physical Medium Dependent sublayer, PMD sublayer, single-mode fiber, SMF.
Keywords: Local area networks (Computer networks); Metropolitan area networks (Computer networks)